Voice of the Leopard : African Secret Societies and Cuba - Miller, Ivor (Book collections on Project MUSE., 2009)
In Voice of the Leopard: African Secret Societies and Cuba, Ivor L. Miller shows how African migrants and their political fraternities played a formative role in the history of Cuba. During the eighteenth and nineteenth centuries, no large kingdoms controlled Nigeria and Cameroon's multilingual Cross River basin. Instead, each settlement had its own lodge of the initiation society called Ékpe, or "leopard," which was the highest indigenous authority. Ékpe lodges ruled local communities while also managing regional and long-distance trade. Cross River Africans, enslaved and forcibly brought to